Distributional changes in the gender wage gap - Sonja Kassenböhmer; Mathias Sinning (Institute for the Study of Labor (IZA), 2010)
This paper analyzes changes in wage differentials between white men and white women over the period 1993-2006 across the entire wage distribution using Panel Study of Income Dynamics (PSID) data. We decompose distributional changes in the gender wage gap to assess the contribution of observed characteristics measuring individual productivity. We find that the gender wage gap narrowed by more than 13 percent at the lowest decile and by less than 4 percent at the highest decile. The decomposition results indicate that changes in the gender wage gap are mainly attributable to changes in educational attainment at the top of the wage distribution, while a sizeable part of the changes is due to work history changes at the bottom. Our findings suggest that the educational success of women could reduce the gender wage gap at the bottom of the distribution both before and during the 1990s but did not trigger a strong decline at the top of the distribution until today.
Keywords: C21; J16; J31; 330; gender wage gap; decomposition analysis; unconditional quantile regression